1999
DOI: 10.1016/s0022-5223(99)70099-1
|View full text |Cite
|
Sign up to set email alerts
|

The influence of regional spinal cord hypothermia on transcranial myogenic motor-evoked potential monitoring and the efficacy of spinal cord ischemia detection

Abstract: Detection of spinal cord ischemia with transcranial myogenic motor-evoked potentials is not delayed at moderate subdural hypothermia in pigs. At a cerebrospinal fluid temperature of 28 degrees C, transcranial myogenic motor-evoked potential amplitudes are increased. Further cerebrospinal fluid temperature decreases result in progressive amplitude decreases and latency increases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
30
0
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 28 publications
(28 reference statements)
0
30
0
1
Order By: Relevance
“…This applies to all disc cup EEG electrodes and most type i corkscrew electrodes and EEG needle electrodes (Table 1). EEG disc cup electrodes and corkscrew electrodes DELETIS and CAMARGO, 2001;HICKS et al, 1992;KOTHBAUER et al, 1997;MEYLAERTS et al, 1999;PECHSTEIN et al, 1996; VAN-DONGEN et al, 1999) are used for TES in almost all centres. Table 1 shows that the mean Vth of 56 V with large contact-surface electrodes is increased to 251 (+250%) for the corkscrew (type i) and single EEG needle electrodes and to 347 (+346%) for the EEG disc cup surface electrodes.…”
Section: Discussionmentioning
confidence: 99%
“…This applies to all disc cup EEG electrodes and most type i corkscrew electrodes and EEG needle electrodes (Table 1). EEG disc cup electrodes and corkscrew electrodes DELETIS and CAMARGO, 2001;HICKS et al, 1992;KOTHBAUER et al, 1997;MEYLAERTS et al, 1999;PECHSTEIN et al, 1996; VAN-DONGEN et al, 1999) are used for TES in almost all centres. Table 1 shows that the mean Vth of 56 V with large contact-surface electrodes is increased to 251 (+250%) for the corkscrew (type i) and single EEG needle electrodes and to 347 (+346%) for the EEG disc cup surface electrodes.…”
Section: Discussionmentioning
confidence: 99%
“…However, despite these temperature effects on tcMEPs, the duration in which to perceive the spinal cord ischemia in hypothermia was found not to differ, compared with the normothermic group. 26 We did not determine hypothermia in our cases during their temperature follow-ups performed with TOF. We have limited knowledge about the effects of hypoxia on the tcMEP responses in humans.…”
Section: Resultsmentioning
confidence: 89%
“…Hypothermia increases tolerance to spinal cord ischemia by reducing the metabolic rate [28], inhibiting glutamate and dopamine release [29,30], producing heat shock proteins [31], and by many other unknown mechanisms [32]. Spinal cord cooling can be attained by either systemic cooling [6] or direct local cooling [16]. A number of studies have demonstrated a beneficial effect of local cooling by intrathecal perfusion with cold solution [33].…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we developed a rabbit spinal cord ischemia model by occluding the lumbar arteries with snare devices. This selective occlusion of lumbar arteries has been used in pigs [16] but not in rabbits before. In this model, hemodynamic changes during ischemia are minimal because the blood flow in the aorta is intact.…”
mentioning
confidence: 99%